Invisible children : advocating an interventionist policy in Africa - Alex Bookbinder (2012)
Activist organisation Invisible Children is calling for American military cooperation to arrest notorious war criminal Joseph Kony in the Democratic Republic of Congo. This is poorly conceived policy, is a misuse of resources, and may potentially destabilising for global supply chains.